ANALISA PERBANDINGAN PENGUKURAN TEKANAN ANNULUS TEORI DAN LANGSUNG PADA PROSES PENGEBORAN MINYAK BUMI - Muhajir, Khairul; Sentono, Sugijarto Prawiro; Taufik, Esa (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
In oil drilling process, the application of pressure measurements in in space between formation borehole and drill pipe (annulus) is very important. The correlation of predicted and measured annulus pressures is a very complex. The engineer’s knowledge of oil drilling process is very important to understand annulus pressure change and their effects will influence the accuracy of annulus pressure predictions. Factors that should be considered include the monitoring and collection of rig-site information such as density, viscosity of mud, drilling depth, flow rate, and drill pipe rotation. The author collects the data and made the analysis with supporting documents. The research concludes that there are differences between predicted and measured annulus pressure. The most dominant factor is mud density that measured on surface and the one in the bore hole. The mud density in the borehole is influences by another material from rubbish and cutting. The equation is not corrected by the influences of that another material. The higher of percentage of rubbish in the bore hole will be caused the higher of mud density; hence the ECD and annulus pressure will be higher also. The amount of rubbish also influenced by viscosity, flow rate, and drill pipe rotation.